Intracellular Shuttle: The Lactate Aerobic Metabolism - Rogério Santos de Oliveira Cruz; Rafael Alves de Aguiar; Tiago Turnes; Rafael Penteado Dos Santos; Mariana Fernandes Mendes de Oliveira; Fabrizio Caputo (The Scientific World Journal)
Lactate is a highly dynamic metabolite that can be used as a fuel by several cells of the human body, particularly during physical exercise. Traditionally, it has been believed that the first step of lactate oxidation occurs in cytosol; however, this idea was recently challenged. A new hypothesis has been presented based on the fact that lactate-to-pyruvate conversion cannot occur in cytosol, because the LDH enzyme characteristics and cytosolic environment do not allow the reaction in this way. Instead, the Intracellular Lactate Shuttle hypothesis states that lactate first enters in mitochondria and only then is metabolized. In several tissues of the human body this idea is well accepted but is quite resistant in skeletal muscle. In this paper, we will present not only the studies which are protagonists in this discussion, but the potential mechanism by which this oxidation occurs and also a link between lactate and mitochondrial proliferation. This new perspective brings some implications and comes to change our understanding of the interaction between the energy systems, because the product of one serves as a substrate for the other.